2016
DOI: 10.1038/onc.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the RB-E2F pathway in breast cancer

Abstract: Mutations of the retinoblastoma tumor suppressor gene (RB1) or components regulating the CDK-RB-E2F pathway have been identified in nearly every human malignancy. Re-establishing cell cycle control through CDK inhibition has therefore emerged as an attractive option in the development of targeted cancer therapy. The most successful example of this today is the use of the CDK4/6 inhibitor palbociclib combined with aromatase inhibitors for the treatment of estrogen receptor-positive breast cancers. Multiple stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
142
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 66 publications
4
142
0
Order By: Relevance
“…E2F transcription factors are not frequently mutated, but may be involved large-scale chromosomal aberrations such as loss of 16q [Johnson et al 2016]. p21 Cip1 expression is frequently reduced as a consequence of TP53 mutation [Musgrove et al 1995] or Myc overexpression [Mukherjee and Conrad, 2005], and p27 Kip1 expression is reduced as a result of HER2 amplification [Chu et al 2008].…”
Section: Cyclin-dependent Kinases and The Cell Cyclementioning
confidence: 99%
See 3 more Smart Citations
“…E2F transcription factors are not frequently mutated, but may be involved large-scale chromosomal aberrations such as loss of 16q [Johnson et al 2016]. p21 Cip1 expression is frequently reduced as a consequence of TP53 mutation [Musgrove et al 1995] or Myc overexpression [Mukherjee and Conrad, 2005], and p27 Kip1 expression is reduced as a result of HER2 amplification [Chu et al 2008].…”
Section: Cyclin-dependent Kinases and The Cell Cyclementioning
confidence: 99%
“…Accumulating evidence also shows roles for the E2F transcription factors beyond that in the cell cycle [Johnson et al 2016], including roles in promoting invasiveness [Yoon et al 2006] and metastatization [Andrechek, 2015].…”
Section: Cyclin-dependent Kinases and The Cell Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicated that response of breast cancer cells to PD-0332991 is associated with expression pattern of CDK4/6-pRb-E2F pathway mediated genes such as Rb1, CDKN2A, and cyclin D1 (25)(26)(27). In cell cycle, mitogenic signals induce cyclin D1 gene (CCND1) expression to initiate G1-S transition.…”
Section: Discussionmentioning
confidence: 99%